(untitled) (Research, Society and Development, 2019)
The aim of the study was to evaluate the epidemiological profile of food botulism in Brazil from 2001 to 2015. This is a retrospective, observational and descriptive study, in which the information used for data collection was available on the website. The Informatics Department of the Unified Health System, through the National System of Notification Disorders (SINAN/DATASUS). There were 74 confirmed cases of food botulism in Brazil, being the highest prevalence of botulism identified in the Southeast region of the country with 45.9% of notifications. The state of São Paulo was the one with the most notifications of the disease, with 28.4% of the cases reported in the country, followed by Paraná (13.0%) and Santa Catarina (13.0%). Regarding the months of the year, it was observed that in 47.3% of the cases, there was involvement by the disease between January and March. The case fatality rate was 16.2%. Regarding the mortality rate, we found an index of 0.12/cases per 100,000 inhabitants. Given the knowledge of the epidemiological profile of the disease it is important to establish strategies of prevention of disease in primary health care services, disseminating information regarding the importance and care in food handling.